2017
DOI: 10.1002/adhm.201601251
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐Layered Nanocomposite Hydrogel Scaffold for the Concurrent Regeneration of Cementum, Periodontal Ligament, and Alveolar Bone

Abstract: A tri-layered scaffolding approach is adopted for the complete and concurrent regeneration of hard tissues-cementum and alveolar bone-and soft tissue-the periodontal ligament (PDL)-at a periodontal defect site. The porous tri-layered nanocomposite hydrogel scaffold is composed of chitin-poly(lactic-co-glycolic acid) (PLGA)/nanobioactive glass ceramic (nBGC)/cementum protein 1 as the cementum layer, chitin-PLGA/fibroblast growth factor 2 as the PDL layer, and chitin-PLGA/nBGC/platelet-rich plasma derived growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 36 publications
1
120
0
Order By: Relevance
“…Along with the required growth factors, the implantation of tissue‐/structure‐mimicking biomaterials would also benefit the recreation of a suitable local matrix microenvironment. An interesting example that supports the proof‐of‐concept that anatomically shaped that tooth scaffolds can be used for periodontal regeneration by cell homing is the trilayered scaffold reported by Sowmya et al for concurrent regeneration of the three types of periodontal tissues; each layer was specifically designed to contain chitin/poly(lactic‐ co ‐glycolic acid) (chitin‐PLGA) and/or nanobioactive glass ceramic (nBGC) components. A layer composed of chitin‐PLGA/nBGC loaded with recombinant human cementum protein‐1 was applied to generate cementum, and similar components combined with PRP were included to regenerate the bone.…”
Section: Harnessing Endogenous Stem Cells Via In Vivo Cell‐materials Imentioning
confidence: 77%
See 2 more Smart Citations
“…Along with the required growth factors, the implantation of tissue‐/structure‐mimicking biomaterials would also benefit the recreation of a suitable local matrix microenvironment. An interesting example that supports the proof‐of‐concept that anatomically shaped that tooth scaffolds can be used for periodontal regeneration by cell homing is the trilayered scaffold reported by Sowmya et al for concurrent regeneration of the three types of periodontal tissues; each layer was specifically designed to contain chitin/poly(lactic‐ co ‐glycolic acid) (chitin‐PLGA) and/or nanobioactive glass ceramic (nBGC) components. A layer composed of chitin‐PLGA/nBGC loaded with recombinant human cementum protein‐1 was applied to generate cementum, and similar components combined with PRP were included to regenerate the bone.…”
Section: Harnessing Endogenous Stem Cells Via In Vivo Cell‐materials Imentioning
confidence: 77%
“…The assessment of this scaffold using a rabbit periodontal defect model showed that the cell‐free construct induced complete regeneration of the hybrid tissues in the periodontium (Fig. ) . Based on available data, chemoattractive constructs have been proven effective in the treatment of periodontal defects, and further research should consider the translation of these proof‐of‐concept studies to clinical use.…”
Section: Harnessing Endogenous Stem Cells Via In Vivo Cell‐materials Imentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address the highly hierarchical structure of the native periodontium, the field of periodontal regeneration has moved from monophasic constructs to multiphasic constructs, whereby compartmentalization is generated in order to guide the healing process in a specific manner for each component of the periodontal tissue (bone, ligament and cementum) . Multiphasic architectures should encourage tissue regeneration between the construct's subcomponents, thus improving intercalation and functional integration of the different tissues in order to replicate the architecture of the native periodontium .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have also reported bioactive glass ceramic-based composites for the regeneration of hard and soft tissues. For instance, it was shown that a porous tri-layered nanocomposite scaffold composed of chitin poly (lactic-co-glycolic acid)/nano bioactive glass ceramic/cementum protein 1 as the cementum layer, chitin-poly (lactic-co-glycolic acid)/fibroblast growth factor 2 as the periodontal layer, and chitin-poly (lactic-co-glycolic acid)/nano bioactive glass ceramic/platelet-rich plasma derived growth factors as the alveolar bone layer, is cytocompatible and favored cementogenic, fibrogenic, and osteogenic differentiation of human dental follicle stem cells (97). The scaffold with growth factors demonstrates complete defect closure and healing with new cancellous-like tissue formation and formation of new cementum, fibrous periodontal tissue, and alveolar bone with well-defined bony trabeculae in comparison to the other three groups, upon implantation into rabbit maxillary periodontal defects.…”
Section: Bioceramics Applications In Tissue Engineeringmentioning
confidence: 99%